The importance of teamwork, communication, and culture in failure to rescue in the elderly - Ghaferi, Amir A. (Br J Surg, 2015)
INTRODUCTION: Surgical mortality increases significantly with age. Wide variations across hospitals in mortality rates suggest potential levers for improvement. Failure to rescue has been posited as a potential mechanism underlying these differences. METHODS: We performed a review of the literature evaluating surgery, mortality, failure to rescue, and the elderly. We then included a review of ongoing studies and unpublished work aiming to better understand the mechanisms underlying variations in surgical mortality in elderly patients. RESULTS: Multiple hospital macro system factors, such as nurse staffing, available hospital technology, and teaching status are associated with differences in failure to rescue rates. There is emerging literature regarding important micro system factors associated with failure to rescue. These are grouped into three broad categories, hospital resources, attitudes, and behaviours. On-going work to produce interventions to reduce variations in failure to rescue rates include a focus on teamwork, communication, and safety culture. Researchers are using novel mixed-methods approaches and theories adapted from organizational studies in high reliability organizations in an effort to improve the care of elderly surgical patients CONCLUSION: While elderly surgical patients experience failure to rescue events at much higher rates than their younger counterparts, patient level effects do not sufficiently explain these differences. Increased attention on the role of organizational dynamics in the hospitals’ ability to rescue these high risk patients will establish high yield interventions aimed at improving patient safety.